2021
DOI: 10.1177/15562646211005253
|View full text |Cite
|
Sign up to set email alerts
|

“Like a Sheriff in a Small Town”: Status, Roles, and Challenges of Ethics Committees in Academic Colleges of Education

Abstract: In recent years, Research Ethics Committees in academic colleges of education have constituted to review research proposals in the field of education. Yet, little is known about their work, composition, challenges, and relationships with external partners. This study explores the views and attitudes of 13 members and chairpersons of Research Ethics Committees in colleges of education in Israel, and two policy makers at the Ministry of Education about their roles, responsibilities, challenges, and limitations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Moreover, the “ethics-as-process framework” challenges the position of REC and their rationale (Sperling, 2021), as well as common ethical principles, most notably informed consent. The philosophical justification for such an approach stems from determining the ethical as a process in the making, not subject to an a priori ruling or judgement regarding research ethics (Johansen & Frederiksen, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the “ethics-as-process framework” challenges the position of REC and their rationale (Sperling, 2021), as well as common ethical principles, most notably informed consent. The philosophical justification for such an approach stems from determining the ethical as a process in the making, not subject to an a priori ruling or judgement regarding research ethics (Johansen & Frederiksen, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies had emphasized the lack of formal training and the nature of the broad discussion on ethics that may occur in the work of Research Ethics Committees (Sperling 2021) and the appearance of inconsistencies between ethics committees' reviews (Trace and Kolstoe 2017). Furthermore, other studies showed that the heterogeneity of opinions between ethics board members, especially when the protection of the institution's interests are questioned, may lead to poor relations and mistrust between ethics committees and researchers (Guillemin et al 2012).…”
Section: Introductionmentioning
confidence: 99%